The Images of Climate Change over the Last 20 Years: What Has Changed in the Portuguese Press? - Lopes, LS (2023)
Over the past three decades, there has been a significant increase in political and media attention towards climate change. The media has been instrumental in shaping, reproducing, and influencing the political and cultural comprehension of this phenomenon. While previous research has concentrated primarily on the textual content of news articles, this study focuses on the use of images in climate communication. It is based on the belief that images can combine facts and emotions, engaging audiences and adding narrative complexity to verbal claims. With focus on climate imagery, a content analysis was conducted on 1010 images used by a Portuguese newspaper (Público) between January 2000 and May 2022 to visually cover climate change. The purpose of the analysis was to identify the visual frames used by the newspaper to frame the issue. The primary findings indicate that 35.5% of the images analyzed employ a frame that dramatizes the effects of climate change, evoking anxiety and vulnerability. However, there is evidence of a growing body of scientific literature that challenges and refutes the sensationalist and demoralizing narrative, resulting in the development of novel methods of communicating the phenomenon. Compared to the preceding period (2000–2005), the proportion of visual frames depicting potential solutions and adaptation strategies has increased substantially over the past three years (2020–2022) by 16.3%. © 2023 by the authors.